Konstruksi Realitas Dunia Kerja Platform Digital: Startwork.id sebagai Media Massa dalam Kehidupan Digital - Dwi Prasetyo; Zihan Haliza (Jurnal Nomosleca, 2026)
This study aims to analyze how Startwork.id constructs the reality of the world of work as a digital mass media platform within the context of digital life. The research adopts a descriptive qualitative approach, employing thematic and interpretative analysis of ten Startwork.id editorial contents selected purposively, supplemented by limited interviews for meaning triangulation. The findings indicate that Startwork.id consistently frames the world of work as a dynamic, competitive space that requires continuous individual readiness. Narratives of success and ideal careers are built through the logic of self-improvement, professionalism, productivity, and personal responsibility, while the ideal worker is normalized as adaptive, competently relevant, proactive, and job-ready. At the same time, structural issues such as unequal access to employment, precarization, and power relations in the digital labor market are relatively absent from the platform’s narratives. This study affirms that digital work platforms do not merely function as information intermediaries but also act as communication agents that produce, select, and normalize particular meanings of work, career, and professional identity. Theoretically, this study extends the application of social construction of reality theory to the realm of local digital work platforms; practically, it offers a basis for critical reflection for platform managers, educational institutions, and young generations in engaging with career narratives in digital spaces.